Efficiency improvement of using unmanned aerial vehicles by distribution of tasks between the cores of the computing processor - Zhuravska, Iryna; Borovlyova, Svitlana; Kostyria, Mykhailo; Koretska, Oleksandra (Technology audit and production reserves, 2017)
The object of research is the computer system of unmanned aerial vehicles (UAVs). Most modern UAVs are based on 2- or 4-core single-chip processors, between which between which the OS automated scheduler tries to evenly distribute computational tasks. One of the most problematic places in the described process is that the first core can instantly become extremely congested in the event of an urgent task from the UAV control system. Therefore, the subject of research is complex indicators of the state of the processor cores for various algorithms of task distribution proposed between the cores of a multicore single-chip processor. In the course of the research, methods for simulating the dispatching of tasks processed by the UAV computer system based on a quad-core single-chip processor are used. The expediency of using the energy of the measuring signal from piezoelectric sensors for partial compensation of the consumed energy by the UAV computer system is investigated and justified. To evaluate the effectiveness of measures taken to increase the efficiency of the use of computer system components, the HWMonitor utility is used. According to the research results from the developed certain optimal algorithm, which differs from the others by reserving the resources of the 1st core of a multi-core single-chip computing processor for calculations of primary importance. The use of such calculation algorithm provides an increase in flight time by 3.1 minutes and increases the range of professional tasks by 1.3 min (for UAV DJI Phantom 4). In comparison with similar known solutions, the proposed algorithm improves the UAV stable behavior in critical applications (loss of ground control, the occurrence of obstacles, the impossibility of obtaining GPS coordinates in the areas of radio electronic warfare, etc.).